Archaia Phusis: the original nature of the soul in Plato’s Middle Dialogues - Körner, H (2023)
This thesis investigates Plato’s conception of an original nature (archaia phusis) of the soul in the middle dialogues Symposium, Phaedo, Republic, and Phaedrus. The originally Hippocratic expression refers to a temporally prior state that represents a normative standard, and features prominently in Aristophanes’s speech in the Symposium (191d1–2; 192e9; 193c5; 193d4). In Republic X’s Glaucus simile (611b1–612a7, cf. Tim. 90d5), it designates the soul’s condition of phronēsis and true virtue which we possessed at a prior point, are currently deficient in, and desire or should desire to restore.